Discharge education for older people and family members in emergency department: A cross-sectional study. Issue 4 (October 2015) - Palonen, Mira; Kaunonen, Marja; Helminen, Mika; Åstedt-Kurki, Päivi
Highlights Older patients and family members receive little ED discharge education. Discharge education is associated with higher ED discharge readiness. More focus should be given to discharge education for family members.